Monoclonal antibody-based serological detection of Citrus yellow vein clearing virus in citrus groves - LIU, Zhen; SUNZHU, Yuan-ji; ZHOU, Xue-ping; HONG, Jian; WU, Jian-xiang (Journal of Integrative Agriculture, 2017)
Citrus yellow vein clearing virus （CYVCV） is considered as the causal agent of Citrus yellow vein clearing disease and belongs to the genus Mandarivirus in the family Alphaflexiviridae. Capsid protein （CP） of CYVCV Chongqing isolate （CYVCV- CQ） was produced using a prokaryotic expression system and used as the immunogen for monoclonal antibody （MAb） production. Four highly specific and sensitive murine MAbs and one polyclonal antibody were prepared in this study. Titers of the four MAbs in ascites fluids ranged from 10-6 to 10-7 as determined by indirect enzyme-linked immunosorbent assay （ELISA）. Three serological assays, including dot enzyme-linked immunosorbent assay （dot-ELISA）, tissue blot-ELISA, and double-antibody sandwich （DAS）-ELISA, were developed for quick and reliable detections of CYVCV in citrus samples. The developed dot-ELISA and DAS-ELISA methods could detect CYVCV in the infected citrus leaf crude extracts diluted at 1：2 560 and 1：10 240 （w/v, g mL^-1）, respectively. The detection result of 125 citrus leaf samples collected from citrus groves in Yunnan Province and Chongqing Municipality of China showed that approximately 36% samples were positive for CYVCV. This virus was, however, not＇detected in any sample collected from Zhejiang or Jiangxi Province, China.